Collaborative Governance: Model Pengembangan Ekowisata di Desa Siangan - Anak Agung Gede Oka Wisnumurti; A.A.A Dewi Larantika (Postgraduated Community Service Journal, 2021)
Siangan Village is one of the villages in Gianyar Regency which is being developed into a tourist village. Beautiful natural panoramas, local arts and elements of unique cultural traditions have the potential to be used as spiritual ecotourism attractions. The community of six traditional villages in Siangan, namely Siangan Traditional Village, Lokasrana, Bandung, Sawan, Purna Desa and Munduk Traditional Village are determined to preserve and utilize these cultural resources. Although an inventory and arrangement of cultural heritage has been carried out, it has not been managed optimally. Therefore, community empowerment is needed in packaging cultural heritage, and relevant ecotourism management strategies are applied in Siangan. The Community Partnership Program (PKM) on the Development of Cultural Heritage-based Spiritual Ecotourism is carried out by targeting community groups, especially the pretenders in the Siangan Village area. The target partner is the village head of Siangan. The problems faced by partners are: (1) the cultural heritage has not been packaged and utilized as a support for spiritual ecotourism, (2) the management of the ecotourism potential has not been integrated. This PKM seeks to carry out the packaging of ecotourism potential in Siangan Village, and a partnership-based ecotourism management model (collaborative governance). The method applied is the method of archaeological documentation, counseling and mentoring. The results of this PKM are expected to increase awareness of cultural heritage conservation, ecotourism management partnership models, which have an impact on community welfare.